The incidence and prevalence of diabetes mellitus and related atherosclerotic complications in Korea: a National Health Insurance Database Study. - Bo Kyung Koo (PLoS ONE, 2014)
The incidence and prevalence of type 2 diabetes mellitus (T2DM) and related macrovascular complications in Korea were estimated using the Health Insurance Review and Assessment (HIRA) database from 2007-2011, which covers the claim data of 97.0% of the Korean population.T2DM, coronary artery disease (CAD), cerebrovascular disease (CVD), and peripheral artery disease (PAD) were defined according to ICD-10 codes. We used the Healthcare Common Procedure Coding System codes provided by HIRA to identify associated procedures or surgeries. When calculating incidence, we excluded cases with preexisting T2DM within two years before the index year. A Poisson distribution was assumed when calculating 95% confidence intervals for prevalence and incidence rates.The prevalence of T2DM in Korean adults aged 20-89 years was 6.1-6.9% and the annual incidence rates of T2DM ranged from 9.5-9.8/1,000 person-year (PY) during the study period. The incidence rates of T2DM in men and women aged 20-49 years showed decreasing patterns from 2009 to 2011 (P<0.001); by contrast, the incidence in subjects aged 70-79 years showed increased patterns from 2009 to 2011 (P<0.001). The incidence rates of CAD and CVD in patients newly diagnosed with T2DM were 18.84/1,000 PY and 11.32/1,000 PY, respectively, in the year of diagnosis. Among newly diagnosed individuals with T2DM who were undergoing treatment for PAD, 14.6% underwent angioplasty for CAD during the same period.Our study measured the national incidences of T2DM, CAD, CVD, and PAD, which are of great concern for public health. We also confirmed the relatively higher risk of CAD and CVD newly detected T2DM patients compared to the general population in Korea.